Histological evaluation of the effects of systemic administration of strontium ranelate on bone healing in rat tibia fractures - Gul, Mehmet; Tanrisever, Murat; Altintas, Muge Bereket; Istek, Ozmen; Can, Umit Koray; Ozcan, Erhan Cahit; Karabulut, Burak (Univ Zulia, Facultad Ciencias Veterinarias, 2026)
This study aimed to investigate the effects of strontium renelate, a known bisphosphonate-like agent with effects on bone tissue, on bone fracture and defect healing using histological methods. For this purpose, a fracture study was conducted using 28 rats, each consisting of healthy controls (n = 7), fracture controls, and treatment groups, receiving strontium dose 1 (450 mg/kg three times per week), and strontium dose 2 (900 mg/kg three times per week). After a six-week fracture healing period, tibia bones were subjected to histological analysis for new bone formation. Data were analyzed using Kruskal Wallis and Mann Whitney U tests. New bone formation was significantly lower in the fracture groups compared to healthy controls (P < 0.001). An increase in new bone formation ratios was observed in the strontium ranelate-administered groups compared to the fractured controls (P < 0,05). New bone formation was significantly higher in the high-dose strontium ranelate group compared to the low-dose strontium ranelate group (P < 0,05). When histological evaluations and numerical analyses were evaluated together, it was concluded that systemic strontium ranelate administration significantly accelerated new bone formation and maturation processes during fracture healing, depending on the dose used (450 and 900 mg/kg).
Keywords: Strontium renelate; tibia fracture; bone healing; new bone formation; rat